2006
DOI: 10.1007/s00425-006-0406-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultraviolet radiation on photosynthetic performance, growth and sunscreen compounds in aeroterrestrial biofilm algae isolated from building facades

Abstract: The effects of artificial ultraviolet radiation [UVR; 8 W m(-2) ultraviolet-A (UVA), 0.4 W m(-2) ultraviolet-B (UVB)] on photosynthetic performance, growth and the capability to synthesise mycosporine-like amino acids (MAAs) was investigated in the aeroterrestrial green algae Stichococcus sp. and Chlorella luteoviridis forming biofilms on building facades, and compared with the responses of two green algae, from soil (Myrmecia incisa) and brackish water (Desmodesmus subspicatus). All species exhibited decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 53 publications
2
78
1
Order By: Relevance
“…The PAR + UV-A treatment signiWcantly reduced growth rate in Desmodesmus subspicatus, while the addition of UV-B was accompanied by a complete inhibition of growth ). In the present study, no substantial growth was observed in all isolates of M. chthonoplastes exposed to PA and PAB, although the irradiances were similar to those used by Karsten et al (2007). Under PA treatment, where slight bleaching of Wlaments was observed, pigments (Chl a and phycobilins) could have been slightly degraded resulting in a lower autoXuorescence per cell.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…The PAR + UV-A treatment signiWcantly reduced growth rate in Desmodesmus subspicatus, while the addition of UV-B was accompanied by a complete inhibition of growth ). In the present study, no substantial growth was observed in all isolates of M. chthonoplastes exposed to PA and PAB, although the irradiances were similar to those used by Karsten et al (2007). Under PA treatment, where slight bleaching of Wlaments was observed, pigments (Chl a and phycobilins) could have been slightly degraded resulting in a lower autoXuorescence per cell.…”
Section: Discussioncontrasting
confidence: 37%
“…Organisms of 1 to <10 m cell size (M. chthonoplastes cells diameter = 2.6-6.9 m; Karsten and Garcia-Pichel 1996) using UV sunscreens as photoprotective mechanisms can gain considerable physiological beneWts but at the expense of high energetic investment and sometimes with restricted eYciency (Garcia-Pichel 1994). A signiWcant positive correlation between growth rate and MAAs accumulation among diVerent species of aeroterrestrial bioWlm algae was reported by Karsten et al (2007). On the other hand, strain-speciWc physiological responses (pigment, Fv/ Fm and growth) in UVR-exposed Nodularia spumigena were not related to MAAs accumulation (WulV et al 2007).…”
Section: Discussionmentioning
confidence: 93%
“…Compared with the aquatic environment, aeroterrestrial green algae are exposed to harsher environmental conditions, such as diurnally and seasonally high insolation, strong temperature fluctuations and restricted water availability (Karsten et al, 2007a(Karsten et al, , 2007b. Extensive exposure to the atmosphere results in dehydration, which strongly affects photosynthesis and growth.…”
Section: Introductionmentioning
confidence: 99%
“…A presumptive UV-absorbing compound with strong absorption below 300 nm was detected in methanol extracts of Ulva pertusa Kjellman (Ulvophyceae; Han and Han 2005). Another UVabsorbing compound identified as 324-nm mycosporinelike amino acid (MAA) was described in Prasiola crispa (Lightfoot) Kützing and occurs only in numerous green algal members of the Trebouxiophyceae (Karsten et al 2005(Karsten et al , 2007. The absence of this compound in members of the Ulvophyceae and Chlorophyceae suggests a phylogenetic pattern in MAA synthesis.…”
Section: Introductionmentioning
confidence: 99%